PENGARUH PERTUMBUHAN PENJUALAN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Vika Iin Susanti; Eka Oktapiani (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research was conducted with the aim of testing and analyzing the influence of company growth, leverage and company size on tax avoidance. This research uses a quantitative approach method and secondary data originating from food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. Sampling was used using a purposive sampling technique from 10 companies that had met the criteria and observations for 5 years, using multiple regression, testing the data using EViews software version 12. The results of the study stated that sales growth and leverage had no effect on tax avoidance, while company size had an effect on tax avoidance.